Mechanical properties of soft materials - Ser, Nicholas Wei Sheng (2016)
Soft materials, such as silicone gel and hydrogel, are wildly used as tissue mimicking material and energy absorption buffer in impact. In this study, the mechanical properties of silicone gel and hydrogel gel were studied under both quasi-static and dynamic tests to have better understanding of these gels. The silicone gel tested in this study is a kind of A & B mixed gel, whereas the hydrogel are adjusted with various water contents: (a) 90% (b) 92% (c) 94% and (d) 96%. First, the oscillatory shear tests were conducted to study the basic mechanical properties of the gels. Based on storage modulus (elastic property) and loss modulus (viscous property), the linear range were determined with a constant frequency of 1.6 Hz and increasing strain amplitude from 0.1% to 10%. The frequency effects on the two gels were also studied by increasing the test frequency from 0.1 to 100 Hz with a constant strain of 1%. The results show that the shear strain amplitude has little effect on elastic property, but the frequency has significant effect both on storage modulus and on loss modulus. The results are compared with the test data of brain tissue from literature studies. In terms of elastic property, silicone gel shows closer values to brain tissue with the frequency from 0.1 to 5 Hz, whereas hydrogel with water ratio of 92% shows more similar trends at higher frequency. For the viscous property, silicone gel shows higher viscosity than brain tissue, whereas hydrogels show similar increasing tends to the brain tissue with the increasing of frequency. Second, quasi-static compression tests were done at the nominal strain rate of 0.0064 and 0.64. The effects of friction on the contact surface were studied by testing two contact conditions by applying oil or pasting sand paper on the plates. The results show that at low strain rate, it has little effect on the compressive behaviour under both frictional and frictionless contact conditions. The friction on the contact surface shows significant effect on stress strain relationship. The results were also compared with test data of brain from literature studies. At the lower strain rate, brain tissue behaves like silicone gel, whereas at higher strain rate, it behaves like hydrogel with water ratio of 90%. Third, the dynamic behaviour of the two gels was studied under impact tests. An impact setup based on Hopkinson bar was developed. A high speed camera was used to catch the deformation process and two PVDF piezoelectric films were made to measure the impact force. Impact test on gels were conducted at the nominal strain rate of 100, 300 and 1100. To compare with the dynamic behaviour, two quasi-static tests with nominal strain rate of 0.04 and 0.4 were also carried out. Results show strain rate has significant effect on the fracture behaviour, impact force and the deformation mode of the gels.